An Experiment-Based Simplified Method for the Model of Building Groups in CFD Simulation - Hongling Guo; Ying Zhou; Yingxin Li; Zhihui Zhang; Heng Li (Advances in Civil Engineering)
Computational Fluid Dynamics (CFD) has been widely used in the simulation and analysis of community or urban wind environments. However, the CFD-based wind simulation of large-scale building groups usually consumes a lot of computing resources with high computing costs. To improve the efficiency of CFD-based wind simulation, this paper presents an experiment-based simplified method for the model of building groups. Two rectangular buildings are adopted as the basic unit and four control parameters (B/L, W/L, H/L, and D/L) are selected as the experiment factors to analyze the geometrical relationship of the two buildings. Note that L, W, and H, respectively, represent the windward edge length, width, and height of a building, B is building interval distance, and D is the distance between two building center axes. Then, a single factor experiment and an orthogonal experiment are designed and performed to determine the reasonable value range of each factor. Based on the experiment results and actual situation, the value ranges of four factors for the simplification of building group models are determined as follows: B/L∈{0, 1.5}, W/L∈{0, 2}, D/L∈{0, 0.25}, and H/L∈{0, 1}. Furthermore, a real case is presented to evaluate the performance of the proposed simplified method. The results indicate that the simplified method is able to improve the efficiency of CFD-based wind simulation of building groups, with the number of buildings decreasing from 620 to 395 (by 36.3%), and the number of tetrahedral grids decreasing from 8,832,199 to 7,766,778 (by 12.1%). Thus, this research contributes to the CFD-based wind simulation method of large-scale building groups and the analysis of the urban wind environment.